Is neutral humanitarian action permissible under Islamic law? - Mohd Kamal, Mohd Hisham (Cambridge University Press, 2015)
In this Opinion Note, Mohd Hisham Mohd Kamal examines neutral humanitarian action during armed conflicts from an Islamic perspective. By analyzing the Qur'an and the Sunnah, he finds that it is permissible to recognize a neutral third party. More ever, Mohd Hisham Mohd Kamal considers siyasah al-shar'iyyah and maqasid al-shari'ah and finds that neutrality leads to the protection of lives and dignity and is thus compatible with the two concepts. He concludes that neutrality is permissible from the Islamic Perspective.